Determinação de Morainas de Retração na Cordilheira Tres Cruces, Bolívia - Ribeiro, Rafael R; Simões, Jefferson Cárdia (GEOUSP Espaço e Tempo (Online), 2010)
Glacial forms and sediments record glacier past activities, by analyzing such records it is possible to reconstruct glacier maximum extend glaciations. However, most of the glaciers are located in the Polar Regions and mountains areas, where ﬁ eld work is restricted by logistical constraints. An alternative solution for such studies is to integrate ﬁ eld and remotely sensed datasets. Our study proposes the use of cartographic and satellite data for identiﬁ cation of frontal moraines and glacier inventory in a test area located in Cordillera Tres Cruces, Bolivia (67º22’ - 67º32’W e 16º47’- 16º09’S). The existence of retreat moraines in all studied glacial basins indicates that glaciers of the Cordillera Tres Cruces have occupied a broader area during the Holocene. Climatic and topographic controls are clearly identiﬁ ed by looking at the differences in altitude of fronts from glaciers located respectively in opposite sides of the mountain range. This characteristic is probably related to the different solar exposition of the glacier basins. The presence of terminal moraines below 4.500 m of altitude in the Cordillera Oriental, or below 3.500 m in the Cordillera Ocidental, former glaciers extend during the Little Ice Age (1200 – 1800 A.D.).